2022
DOI: 10.1177/08862605221127221
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Mindset and Self-Affirmation Intervention to Reduce Violent and Risky Online Behaviors: The Moderating Role of Previous Victimization

Abstract: The Internet is the setting for several forms of violent and risky behavior among adolescents, such as cyberbullying, sexualized interactions with adults, sexting, and online dating violence. Often, these behaviors are responses to experiences of online victimization. This study examined the differential effects of a wise intervention (WI), combining growth mindset and self-affirmation strategies, on these behaviors for adolescents who had experienced victimization and those who had not. A sample of 1,085 adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A teacher-led program of online activities ( 41 ) with Spanish schoolchildren was able to demonstrate changes across self-reported rates of online grooming and problematic Internet use. A further study ( 42 ) demonstrated that a “growth mindset intervention” was beneficial in promoting resilience for adolescents who had not experienced online victimization at pre-test, but it was not beneficial to those who had been victimized. A follow-up to this study used an online educational intervention (video and text and lasting less than one hour) which focused on online sexual grooming and compared it to a resilience-control intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A teacher-led program of online activities ( 41 ) with Spanish schoolchildren was able to demonstrate changes across self-reported rates of online grooming and problematic Internet use. A further study ( 42 ) demonstrated that a “growth mindset intervention” was beneficial in promoting resilience for adolescents who had not experienced online victimization at pre-test, but it was not beneficial to those who had been victimized. A follow-up to this study used an online educational intervention (video and text and lasting less than one hour) which focused on online sexual grooming and compared it to a resilience-control intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses as professional health workers can collaborate with schools [20] . Nurses can carry out their role as educators and advocates for children, adolescents, parents, teachers and other communities related to preventive actions and efforts, as well as efforts to overcome bullying [21] . Nurses acting as counselors can work together in developing educational programs and carrying out interventions related to bullying as a prevention effort.…”
Section: Introductionmentioning
confidence: 99%